Working experiences of nursing aides in nursing homes: A qualitative study - Yan-ping Wei; Hong Li; Ping Chen; Jing Li; Huiying Chen; Li-Li Chen (Elsevier, 2015)
Objective: To examine how nursing aides in nursing homes perceived their caring work. Methods: Twenty-four nursing aides from one public and one private nursing home in Fuzhou, Fujian Province, China were selected and interviewed in focus groups. Phenomenological analysis was performed. Results: Two themes (positive and negative working experiences) and six sub-themes were drawn: companionship, happiness, trust, achievement, hard work, and grievance. Conclusion: A reasonable work arrangement, positive psychological intervention, and the strengthening of professional, medical and social supports are recommended to improve the work quality and satisfaction of nursing aides in elderly homes.